Evaluation of the broken windows theory in terms of patient safety - Demirel, Erkan Turan; Emül, Eda (My University, 2020)
The broken windows theory introduces an approach applicable to different fields of discipline insofar as it explains how disorder (crime, etc.) occurs in a community and provides a basis from which solutions can be developed to prevent it. Considering the complexity of healthcare systems, irregularities, and rule violations that commonly mark them and put human health at risk, it is important to produce more effective solutions by taking advantage of different perspectives. This study evaluates the applicability of the broken windows theory to patient safety. As this theory can be an effective solution to the medical errors, neglect and rule violations that commonly occur in the delivery of health services, it is important that further research on this subject be performed.
Kitap - Kitap İçinde Yayın (Bölüm ya da Makale)
Keywords: Patient safety; Broken windows theory